Penerapan Bauran Pemasaran Agrowisata Jeruk Dekopon di Mupu Jeruk Kota Bandung - Ardiansyah, Ikhsan; Suminartika, Eti; Wiyono, Sulistyodewi Nur; Kusumo, Rani Andriani Budi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Agrotourism is an alternative form of tourism that utilizes Indonesia’s natural wealth, such as agriculture, plantations, livestock, and forestry, as attractions for tourists. The number of visitors to Mupu Jeruk agrotourism has fluctuated, tending to stagnate with an average value of 0.0006%. This indicates the need for an effective marketing strategy, especially through the application of marketing mix models. This study aims to describe the implementation of the 7P marketing mix and to identify the 7P marketing mix variables which need improvement. In this study, the researcher used descriptive analysis with a qualitative approach and a case study method. The result shows that (1) The product strategy includes the availability of an orange-picking attraction for visitors and two additional facilities, namely a restaurant and a café. (2) The cost-based pricing strategy applied is still quite affordable for visitors. (3) The location strategy is good because of strategic location and easy access. (4) Promotional strategies via social media still need to be improved and promotional discounts on tourist prices must be consistently carried out. (5) By having a training process and providing appropriate SOPs to employees, the services and employee skills are rated well by visitors. (6) The service process planning consumer convenience, with various payment methods. (7) Mupu Jeruk supports consumer activities well, as seen from the physical facilities including toilets and mushola, but Mupu Jeruk needs to improve their parking area and also add signs in the entrance.